ACQUISITION OF STANDARD MOTOR DIRECTED TO WALK IN CHILDREN WITH AUTISM: A CASE STUDY (Fiep Bulletin - online, 2012)
The aim of this study is to evaluate the motor pattern in directed walk in children with autism and identify effective instructional procedures to facilitate the acquisition, retention and transfer the locomotor ability during the variability of motor action, It was a case study. The sample was consisted of Five male children with a clinical diagnosis of autism (CID F.84.0) assisted by the Extension in Motor Activity Project to children and teenagers with autism (PREMAUT) from the physical education course of Federal University of Alagoas in Maceió. The materials and methods used were: documentary analysis, semi – structed interviews with parents and guardians and the application of motor tests based in the development of the Gallahue and Ozmun’s motor (2005). The results showed that 80% of the sample has difficulties in performing visuomotor tasks, global motor, balance, body scheme, spatial organization and temporal organization of daily actions. The pre – test showed that 20% of the sample was unable to perfom the tasks of low, medium and high complexity motor, 60% demonstrated in the tasks of low and medium complexity initial stage and 20% demonstrated elementary stage in performing the tasks of low, medium and high motor complexity. The program showed that the structured circuits are more efficient in locomotor skills training. The post – test showed that 40% of the sample in the tasks of low, medium and high complexity are in initial stage, 40% of the sample showed elementary stage and 20% of the sample showed mature stage in implementing the direct walk. It is concluded that the motor learning of locomotor ability, directed walk, is effective when the training is adopted as a strategy structured circuits, regardless of variability of the task and its level complexity.
Keywords: Motor Learning; Walking Directed; Autism